Honey badgers - Odone, Jamison, 1980- (North Carolina : Front Street, 2007)
A boy raised by honey badgers, Maurice and June, describes his slightly odd life.
Primary
Keywords: Adoption -- Fiction; Honey badger -- Fiction; Foundlings -- Fiction; Badgers -- Fiction